Literacy development in kindergarten (2001)
This project was conducted in order to motivate students of transition grade in Hispanoamericano Conde Ansurez School to read through the use of strategies for story-telling. As the sample for this study, the five students who had the lowest language proficiency were selected. According to the results, students improved their English, evidenced understanding of stories read in class and expressed more interest in reading. However, the process has to be continued because reading skills under development need constant practice.